2011
DOI: 10.1007/s10029-011-0786-0
|View full text |Cite
|
Sign up to set email alerts
|

First cases of giant pseudocyst complicating inguinal hernia repair

Abstract: Subtotal surgical removal of the pseudocapsule is a definitive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Ielpo and colleagues described two cases of giant pseudocyst formation after open inguinal hernia repair, both requiring open excision of the pseudocapsule [4]. Surgical intervention was performed in our case due to failure of multiple percutaneous drainage, and the reported success with sclerotherapy in the literature is variable [2][3][4].…”
Section: Discussionmentioning
confidence: 80%
“…Ielpo and colleagues described two cases of giant pseudocyst formation after open inguinal hernia repair, both requiring open excision of the pseudocapsule [4]. Surgical intervention was performed in our case due to failure of multiple percutaneous drainage, and the reported success with sclerotherapy in the literature is variable [2][3][4].…”
Section: Discussionmentioning
confidence: 80%
“…8,9 Pseudocysts have also been reported to form as a complication of inguinal hernia repair. 10 Pseudocysts generally present as protrusions in the abdominal wall located at the site of former incision. The lesion is generally non-tender and develops over a period of months.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the case of our patient, total excision was used to remove the pseudocyst, which has been associated with an excellent prognosis. 10…”
Section: Discussionmentioning
confidence: 99%
“…Chronic fluid collections leading to an inguinal canal pseudocyst are exceedingly rare with only two previous cases reported [ 7 ]. In contrast to the previously reported case, the patient in the present report had undergone a laparoscopic inguinal hernia repair rather than a Lichtenstein approach as reported by Ielpo et al In their experience, this Spanish group found that the pseudocyst was incorporated onto the anteriorly placed mesh.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of the literature revealed a previously published paper which included two similar cases [ 7 ]. The characteristics of these patients and the one of the current report are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%